Unprecedented but Unfulfilled: Refugee Protection and Regional Responses to the Andaman Sea ‘Crisis’ - Madeline Gleeson (Antropologi Indonesia, 2017)
In May 2015, a situation unfolding in the Bay of Bengal and Andaman Sea – since dubbed the Andaman Sea ‘crisis’ – threw into sharp relief the limitations of the region’s willingness and capacity to respond to large scale movements of refugees and irregular migrants. More than 5,000 Rohingya refugees and Bangladeshi migrants became stranded at sea, after people smugglers abandoned their boats and nearby countries refused to let them land. Ultimately it fell to a handful of the most affected countries in the region – Indonesia, Malaysia and Thailand in particular – to take the lead in initiating a regional response. This article explores this response, and how the Andaman Sea crisis and its subsequent fallout affected approaches to refugee protection in the Asia-Pacific. It focuses on the multilateral fora and mechanisms deployed to resolve the situation, and whether they have improved the region’s preparedness to respond to such events in the future. It demonstrates that the crisis forced some states to reconsider their roles as ‘transit countries’, recognise displacement and refugees as issues of pressing concern, and reassess the strength of their multilateral cooperation processes. However, many of the commitments made since 2015, unprecedented as they were, remain unfulfilled. Whether the region emerged better prepared to respond to such situations in the future is yet to be seen.Keywords: Rohingya, migration, refugees, cooperation, ASEAN, Bali Process